The Boltzmann equation and Cosmic Microwave Background - Valenzuela, Mississippi (2023)
Observations on the anisotropies of the Cosmic Microwave Background (CMB) have become a fundamental tool in Cosmology. We present a brief description of the mformalism necessary to understand the evolution of the anisotropies, and how their power spectrum gives us information about the evolution and composition of the universe.